Transformation processes in managing regional economy - N. P. Molchanova (Вестник Российского экономического университета имени Г. В. Плеханова)
The goal of the article is to study academic foundations of territorial management established in the process of evolution of home regional economic science and specific features of their practical implementation at different stages of economic development of our country. By using the dialectic method of cognition and system approaches it is possible to reveal the diversity of historically formed scientific views dealing with such issues as shaping and managing administrative – territorial units in Russia as a federal state, to analyze positions of different scientists in defining certain basic categories of regional science, to systematize terms and ground the author’s position in defining the term ‘region’ in interconnection with other single-ordinal scientific categories. The author investigated the laws of functioning and trends of development of regional economy in connection with problematic issues of designing the concept of spatial development of the Russian Federation. The place of macro-region as a key taxonomic unit for studying the spatial structure of national economy is being identified, as well as its principle role as a forming link in the system of sub-federal management during the shift to the 6th technological structure. The author grounds the expediency of further research in the context of renewal of methodological tools and use of proposed organizational innovation aimed at development of basic provisions of science about regions in order to optimize territorial structure of economy and raise the quality of management of spatial development of the Russian Federation in conditions of digital economy formation.